The symbolic dimensions of waterfront regeneration projects: Inter-referencing, legitimating strategies and circulating practices in three Latin American megaprojects - Jajamovich, Guillermo Paz (2025)
This paper provides a comparative analysis of three symbolic dimensions of waterfront regeneration projects in Latin American cities: the inter-referencing practices alluded to in relation to projects from elsewhere, legitimating strategies that are discursively and materially constructed to present these projects as socially distributive, and subsequent approaches to leverage lessons from these experiences and re-circulate practices to other places. Following recent literature on urban megaprojects, policy mobility and inter-referencing we postulate that urban megaprojects production and legitimation involves material and symbolic, as well as territorial and relational processes, including the mobilisation of symbols, representations and images that generate consensus and mitigate criticism and resistance.